Using RNA sample titrations to assess microarray platform performance and normalization techniques - Shippy, Richard; Fulmer-Smentek, Stephanie; Jensen, Roderick V; Jones, Wendell D; Wolber, Paul K; Johnson, Charles D; Pine, P Scott; Boysen, Cecilie; Guo, Xu; Chudin, Eugene; Sun, Yongming Andrew; Willey, James C; et al. (Nature biotechnology, 2006)
We have assessed the utility of RNA titration samples for evaluating microarray platform performance and the impact of different normalization methods on the results obtained. As part of the MicroArray Quality Control project, we investigated the performance of five commercial microarray platforms using two independent RNA samples and two titration mixtures of these samples. Focusing on 12,091 genes common across all platforms, we determined the ability of each platform to detect the correct titration response across the samples. Global deviations from the response predicted by the titration ratios were observed. These differences could be explained by variations in relative amounts of messenger RNA as a fraction of total RNA between the two independent samples. Overall, both the qualitative and quantitative correspondence across platforms was high. In summary, titration samples may be regarded as a valuable tool, not only for assessing microarray platform performance and different analysis methods, but also for determining some underlying biological features of the samples.